(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
Smart cities, one of the key application areas of 5G and IoT technologies, have at their core the goal of improving quality of life, creating collaborative solutions, and addressing resource constraints. Examples of some of the many services integrated into the network of a typical smart city are related to smart health, smart transportation, smart buildings, smart hotels, smart industry, smart universities, etc. The new era of wireless mobile telecommunication technology and the IoT ecosystem is driving the opportunities for smart cities to not only solve existing problems but also create new services and functionalities that are out of the box and invisible to the end user. The main objective of this paper is to explore the role of 5G and IoT in smart cities. The market environment, key business developments, and trends related to the key smart cities’ enablers, IoT and 5G, are presented. An in-depth literature review followed by a discussion is substantiated with synthesised research findings on the current development, 5G coverage, use and deployment of IoT in smart cities, and forecasting the evolution of its application in smart cities.